ANALISIS NILAI SOSIAL PADA NOVEL BILA MALAM BERTAMBAH MALAM KARYA PUTU WIJAYA DENGAN PENDEKATAN MIMETIK (SATU Press Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2021)
Every literary work must have the social values ​​of life contained in it, whether conveyed implicitly or explicitly. Like the novel Bila Malam Bertambah Malam by Putu Wijaya, it contains many social values ​​and so on. With these problems, this research article is written to discuss